Provision Of Women's Reproductive Health Education Through “Kulwhapp” In Nasyiatul's Healthy Adolescent Service Group (Phasmina) PDNA Kebumen Regency - Qomar, Umi Laelatul; Na’mah, Lutfia Uli (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Reproductive health is a state of complete physical, mental and social well-being and is not merely free from disease or disability in all matters relating to the reproductive system, function and process. The World Health Organization (WHO) states that the problem of poor women's reproductive health has reached 33% of the total burden of disease that affects women worldwide. Maintaining reproductive health is absolutely necessary. Reproduction is a way to maintain human offspring on earth so that maintaining women's reproductive health is a part of preserving human civilization and health. The purpose of this community service is to increase the knowledge of phasmina members about reproductive health, especially cervical cancer and vaginal discharge. The respondent for this service is a member of the Kebumen Regency PDNA WhatsApp group. The results of this community service show an increase in knowledge about cervical cancer and vaginal discharge.